FRI0726-HPR DOES ART THERAPY MAKE A DIFFERENCE IN THE MANAGEMENT OF CHILDREN AND YOUNG PEOPLE WITH RHEUMATIC DISEASES: A MULTI-SITE SERVICE REVIEW TO EXPLORE THE IMPACT OF ART THERAPY IN TWO TERTIARY PAEDIATRIC RHEUMATOLOGY SERVICES IN SCOTLAND. (June 2019) - Watts, Patricia; Farrugia, Emily; Davidson, Joyce; Leith, Kristin
Abstract : Background: Art therapy interventions in various medical settings are known to contribute to the mental health and wellbeing of patients. In paediatric rheumatology there is a well documented unmet need for psychological support for children and families coping with chronic disease and its treatment. The role that art therapy could have in this provision is unknown and there is no evidence-based research to help understand its potential contribution. The Teapot Trust is a Scottish charity working with paediatric rheumatology services offering art therapy to children and young people with rheumatic diseases. Objectives: This project aimed to evaluate the service provided by art therapists in two tertiary paediatric rheumatology units in Scotland. The objective was to better understand which patients were referred for art therapy; why they were referred; levels of engagement and acceptability of therapy and benefit resulting in improved outcome. Methods: A retrospective review was conducted of referrals received in the period 2012-2018 to art therapy from paediatric rheumatology services. A mixed method approach was used for gathering quantitative, secondary and qualitative data. Quantitative data was collected by collating numerical and demographic information from referral forms; art therapist service databases; and patient medical records. Secondary and qualitative data has been gathered from pre-existing service information; the use of outcome measurement tools; end of therapy evaluations; end of therapy reports and patient feedback forms. Results: The demographics of children seen were as expected in a paediatric rheumatology service with the majority being females with juvenile idiopathic arthritis and on treatment with methotrexate. Peak age of referral was between 7 and 12 years. The majority of referrals were for help with coping either with their diagnosis or the emotional impact. Patient reported outcomes show significant improvements for patients in their social and emotional wellbeing. This review highlighted the limitations of art therapists using a variety of validated and non-validated outcome measures making it difficult to objectively evaluate outcomes. Conclusion: This retrospective multi-site service review demonstrated that art therapy was well used by clinicians as an appropriate psychological support for children and young people with rheumatic diseases. Engagement with the service was good and feedback positive. The review highlighted the challenge of objectively assessing outcomes, with the need to use validated and standardised assessment tools to collect this systematically going forward. A standardised service evaluation framework will be developed to facilitate future service reviews and is hoped that this represents a first step in developing evidence-based research to investigate the impact and benefit of art therapy in supporting children and young people in paediatric rheumatology. Disclosure of Interests: None declared